2015
DOI: 10.2139/ssrn.2701902
|View full text |Cite
|
Sign up to set email alerts
|

Racial Discrimination in the Sharing Economy: Evidence from a Field Experiment

Abstract: In an experiment on Airbnb, we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Workers in the gig economy are especially vulnerable as the supply of workers often outstrips demand, leading to lowered wages . The possibility for more discrimination increases as hiring decisions are made by individuals as opposed to corporate entities with (presumably) more oversight and regulation (Edelman et al 2016). Alamgir & Cairns (2015) find that longterm temporary work perpetuates discrimination and exacerbates economic inequality among Bangladeshi mill workers.…”
Section: Discussionmentioning
confidence: 99%
“…Workers in the gig economy are especially vulnerable as the supply of workers often outstrips demand, leading to lowered wages . The possibility for more discrimination increases as hiring decisions are made by individuals as opposed to corporate entities with (presumably) more oversight and regulation (Edelman et al 2016). Alamgir & Cairns (2015) find that longterm temporary work perpetuates discrimination and exacerbates economic inequality among Bangladeshi mill workers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bertrand and Mullainathan (2004) responded to 1300 employment ads with more than 5000 resumes, some with Black sounding names and others with white, and found that resumes with white names receive 50% more callbacks for interviews. More recently, Edelman, Luca, and Svirsky (2015) found that in the sharing economy, guests with Black sounding names on the website Airbnb were approximately 16% less likely to be accepted than identical guests with white names. Huber (2011) shared the experiences of a Latina participant, who was forced to go to speech classes to correct her accent, Despite her fluency in English several years later, she was removed from the mainstream classroom to participate in "speech therapy" where she was taught the "proper" pronunciation of English words.…”
Section: Color-evasiveness: Expanding a Color-blind Racial Ideologymentioning
confidence: 99%
“…Another recent paper, also by Edelman et al (2015) once again looked at the the Airbnb market for potential racial discrimination but this time focusing on the supply side. In contrast to their earlier study where they looked at discrimination aimed at Airbnb hosts, manifested in a lower listing price, presumably due to lack of demand at a price equivalent to non-minority listings -here they examined the rates of Airbnb host acceptance of a request from Black and White potential guests.…”
Section: Discrimination In the P2p Room Rental Market Of Airbnbmentioning
confidence: 99%